The efficacy of systemic treatment of androgen-dependent dermopathy in women of reproductive age - I. V. Kuznetsova (Медицинский совет, 2015)
Due to the associated serious endocrine and metabolic disorders, hyperandrogenic conditions result in skin lesions and deterioration of the quality of life. The present study aimed to evaluate androgen-dependent dermopathy in patients with various clinical status and determine the effectiveness of therapeutic interventions. The study included 82 patients with ADP who underwent a comprehensive examination with the participation of a dermatologist. The patients underwent general and gynecological examination; dermatologist's examination using ultrasound; skin microtopography; blood tests for the level of peptide and steroid hormones; biochemical blood test to evaluate carbohydrate and fat metabolism. Differentiated treatment was assigned based on the data obtained from the survey: patients with irregular menstrual cycle received COCs containing drospirenone (all women were in need of contraception); for overweight or obese women, the therapy was complemented with metformin; patients with regular ovulatory cycles received flutamide. The treatment demonstrated high efficacy against androgen-dependent dermopathy and safety for the metabolic status.